Possible reasons for the regrettable results of patency of an inside stent in endoscopic transpapillary biliary stenting. Issue 2 (2nd June 2021) - Kuwatani, Masaki; Kawakubo, Kazumichi; Sakamoto, Naoya
Abstract : Endoscopic biliary decompression is a minimally invasive procedure for cholestasis since the first endoscopic retrograde cholangiopancreatography‐guided biliary stenting performed by Soehendra and Reynders‐Frederix. Among the endoscopic biliary decompression, endoscopic transpapillary biliary stenting (EBS), is a mainstream choice and presently has two methods of placement: stenting above the sphincter of Oddi (SO) (suprapapillary) and stenting across the SO (transpapillary). Stent patency is the most important concern for patients, endoscopists and physicians because it can affect both the life prognosis and treatment schedule of patients. Biliary stent occlusion can occur because of several factors. Among them, direct food impaction, biofilm formation, and sludge formation play important roles and are presumed to be theoretically overcome by EBS above the SO. Thus, EBS above the SO is expected to result in a longer patency than EBS across the SO. In the literature, there have been six comparative studies on EBS for distal biliary obstruction in which the stent was placed above or across the SO, including two randomized controlled trials (RCTs) with negative results of stenting above the SO. With respect to EBS for hilar biliary obstruction, there have been no RCTs, whereas four retrospective comparative studies with negative results and four retrospective comparative studies showing positive results of stenting above the SO have been reported. In this review, we focused on EBS above and across the SO, and summarized the positive and negative results of the two types of stenting to promote effective clinical practice and to provide a basis for future studies.